Provision of Health and Social Services for Drug Addicts in the Republic of Macedonia - Dimitrijoska, Suncica; Svetlana Trbojevik; Natasha Bogoevska; Vladimir Ilievsk (European Journal of Multidisciplinary Studies, 2016)
The Republic of Macedonia experienced a rapid growth in drug addiction after its independents in 1991. The complexity of the problem represents a serious challenge for all relevant factors involved in creation of policies as well as actors in delivery of health, education and social services. Provision of necessary service required appropriate amendments of relevant laws based on the adopted international legislation. The most significant legal changes were introduction of the principles of pluralisation of social protection (Law on Social protection, 2004), that enabled emerging of new private for profit and nonprofit actors as providers of services as well as introduction of the principle of decentralization, enabling establishment of services on local level. Additionally, a number of national and local strategies and programs were developed and adopted within the system of health and social protection. These changes contributed to an increase in the number of available services offering variety of treatments responding to the individual needs of beneficiaries. Despite the increase in offered service, the state has yet to respond to the ever rising problem of addicted children. So far, little has been done for this age group of addicts that requires specialized and adjusted service provision. Provided social services are facing the problem in the sustainability of the available services provided within the nongovernmental sector that is mainly financed from foreign funds.